ANALISIS KEMAMPUAN KEUANGAN DAERAH DALAM MEMBIAYAI PENGELUARAN DAERAH DI KABUPATEN KETAPANG - B61110069, DEVY HARINDA (Jurnal Ekonomi Daerah (JEDA), 2015)
ABSTRACT After regional autonomy, local governments have a great opportunity to manaage local financial includes making regional regulationwhich can be changed at any time. These conditions have made high economic costs and local ego in improving its local income. In the implementation in Ketapang regency, the ability to implement regional autonomy is still relatively low in the category of financial viability, and the level of dependence on the central government is still very high in financing development activities, so that the writteris interested to discuss the ability of region financial in defraying the local expending in Ketapang regency, therefore, the writter choses Thesis title "ANALYSIS OF FINANCIAL CAPABILITY IN THE FINANCING OF REGIONAL EXPENDITURE IN THE KETAPANG REGENCY". The formulation of the problem which is analyzed is how is the fiscal capacity in financing the expenditure of Ketapangregion and how the effectiveness and efficiency of regional expenditure in Ketapang regency. The purpose of this study is to analyse the fiscal capacity to finance local expenditure Ketapang and to analyze the effectiveness and efficiency of local finance local expenditure in Ketapang. The results of this study are expected to provide input to the Government of Ketapang in planning and increasing revenue in order to know the effectiveness of policies that have been established, and as a reference for Ketapangregency Government in formulating and setting policy in the future. The analysis used in this research is descriptive method that exposes analyst and provide a comprehensive overview which explain of the actual condition. Also use the specified variable or dependent variable is the structure of local financial revenues, fiscal decentralization, revenue levels and elasticity PAD standard. The data used to support this research is in the form of quantitative and qualitative data in 2000-2012, the data source is a secondary data from the Department of Revenue in Ketapang. The analyzerthat used to answer the question in this research is the analysis of fiscal capacity, analysis of the effectiveness and efficiency analysis. From the analysis of the authors obtained a description that local financial ability to finance spending Ketapang area is still very low, the financial management area when seen by comparing the revenue realization and the target set, very effective.